Discusión guiada para el desarrollo de la expresión oral en estudiantes de la Unidad Educativa “Fe y Alegría” - Miranda Balarezo, Génesis Ariel (2023)
The research work: “Guided Discussion for the Development of oral expression in Students of the Educational Unit “Fe y Alegría”, has as its main objective to develop a proposal based on guided discussion for the development of oral expression in students of eighth grade in the "Fe y Alegría" Educational Unit during the second semester of the 2022-2023 school year. This research was developed with a quantitative approach, descriptive level, the means by which information was collected is field and in terms of its design, it is non-experimental. The population was the eighth-year students of basic education of the “Fe y Alegría” Educational Unit; since the population was finite, the eighth-year students of parallel Basic Education “A” constituted the sample. The techniques used were observation and survey, with the use of a questionnaire and an observation sheet to collect data. The results obtained demonstrate the lack of methodological strategies applied by teachers to students, resulting in oral expression problems. It is concluded that the proposed activities are feasible for application to strengthen expression since they will help improve oral communication.